2012
DOI: 10.21608/jacb.2012.54993
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Analysis of the Photo-Thermosensetive Genic Male Sterility Lines (Ptgms) of Japonica Rice.

Abstract: Combining ability and genetic parameters analysis for agronomic, yield and its component characters were carried out in rice through line x tester analysis of 20 hybrid rice combinations developed by crossing four Photo-Thermosensitive Genic Male Sterility (PTGMS) lines (females) with five male lines / varieties along with parents and check. The 20 hybrids with nine parents were grown in a randomized complete block design with three replications. The experiments were conducted at RRTC in 2010 and 2011growing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Significant variances due to lines x testers interaction for all the traits studied in both seasons except for milling also, grain yield was not significant in 2019 and head rice in 2020, suggesting the presence of significant variances for SCA among hybrids which have a significant and highly significant lines x testers interaction. These results coincide with the findings of (El-Mowafi et al 2012). The significant differences between lines x testers interaction for these traits suggested that specific combining ability is widely attributed to the expression of these traits and gives significance of dominance or nonadditive genetic variances for all these traits (Ghidan and Khedr, 2021).…”
Section: Analysis Of Variancesupporting
confidence: 88%
See 1 more Smart Citation
“…Significant variances due to lines x testers interaction for all the traits studied in both seasons except for milling also, grain yield was not significant in 2019 and head rice in 2020, suggesting the presence of significant variances for SCA among hybrids which have a significant and highly significant lines x testers interaction. These results coincide with the findings of (El-Mowafi et al 2012). The significant differences between lines x testers interaction for these traits suggested that specific combining ability is widely attributed to the expression of these traits and gives significance of dominance or nonadditive genetic variances for all these traits (Ghidan and Khedr, 2021).…”
Section: Analysis Of Variancesupporting
confidence: 88%
“…Also for plant height, 2 out of 24 crosses were found to be negatively significant for SCA effects in first season and three hybrids in second season. The useful negative significant (desirable) values of SCA effects were shown by PR1/IR69625A with mean value of (-18.19) and PR1/Pusa3A with mean value of (-13.14) in 2019 growing season and could be useful to breed short stature cultivars (El-Mowafi et al 2012). For second year, the significant negative values for SCA effects ranged between (-5.00 and -7.50).…”
Section: Estimates Of Specific Combining Ability Effects (Sca)mentioning
confidence: 96%
“…The current study suggested that the sensitive stage of fertility transformation might be from secondary branch primordial to pollen mother cells (PMC) meiosis. This result is in agreement with previous studies reported that the most sensitive stage of temperature phase inducing fertility was around PMC formation stage ( Zhang et al, 1992 , Mou et al, 2001 , Attia et al, 2003 , Yuan et al, 2003 , Ali et al, 1995 , Yuan, 1990 , Si et al, 2011 , Subudhi et al, 1997 , Wang et al, 2003 , Lee et al, 2005 , Pitnjam et al, 2008 , Qi et al, 2014 , Qi et al, 2017 , Fan and Zhang, 2018 , Muhammad et al, 2020 , Yang et al, 2007 , Zhou et al, 2014 , Zhang and Yang, 2014 , Huang et al, 2015 , El-Mowafi et al, 2012 , Murray and Thampson, 1980 , Normile, 2008 , Lei et al, 2014 , Sun et al, 1991 , Tan et al, 2018 , Zhang et al, 2017 , Deng and Fu, 1998 , Attia et al, 2001 , Shahid et al, 2012 , Wu et al, 2015 , Cai et al, 2007 ). It is possible that at these stages, the temperature changes the mutant activates of some physiological processes, which produce fertile pollen grains instead of sterile pollen grains.…”
Section: Discussionmentioning
confidence: 99%
“…Ten Egyptian rice PTGMS lines developed by Professor EL-Mowafi H.F. ( El-Mowafi et al, 2012 ) were used in this study ( Table 1 ). Three of these PTGMS lines were Indica type with donor sterility coming from Pei’ai-64S (Chinese TGMS), while, the other seven were Japonica with sterility source from Nongken-58S (Chinese PGMS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation